Investigation on anthropogenic and opportunistic factors relevant to the incidence of stranded loggerhead sea turtle Caretta caretta along South Tyrrhenian coasts - Serra, Francesco; Iaccarino, Doriana; Fiorito, Filomena; Di Nocera, Fabio; Esposito, Mauro; Cerracchio, Claudia; Esposito, Emanuele; Lambiase, Sara; Degli Uberti, Barbara; Lucifora, Giuseppe; De Carlo, Esterina; Fusco, Giovanna; et al. (Frontiers in Marine Science, 2023)
Caretta Caretta are endangered sea turtles leaving in the Mediterranean Sea. We carried out a study on 195 sea turtles stranded along the coast of Southern Italy, evaluating anthropogenic and opportunistic factors affecting animal health status and probably threatening the species.. More than 60% of the animals showed body injuries mainly caused by marine traffic and fishing. Ingestion of marine litter of various origin was observed in the digestive tract of 38.5% of the turtles investigated. Chelonid herpesvirus 5 was detected (for the first time in this Basin) in 10.8% of the turtles, which were however free from fibropapillomatosis. Analyses on trace elements showed a time reduction in the mean concentrations of Cd and Hg, a decrease in the levels of Pb, and a time-dependent increase of As. Particularly, a site-dependent accumulation of As was detected in turtles from Calabria coasts. A significant correlation between the levels of As in kidney of Campania turtles and their straight line carapace length, indicating a size-dependent accumulation of this metal. Overall, besides dangerous debris items, high levels of trace elements may weaken immune system of Caretta caretta, the most common turtle of the Mediterranean Sea, making it more likely vulnerable to viruses.